Factors impacting revision surgery in patients with chronic rhinosinusitis with nasal polyposis. Issue 3 (14th January 2020) - Loftus, Catherine A.; Soler, Zachary M.; Desiato, Vincent M.; Koochakzadeh, Sina; Yoo, Frederick; Storck, Kristina A.; Schlosser, Rodney J.
Abstract : Background: Surgical treatment of chronic rhinosinusitis with nasal polyposis (CRSwNP) has evolved over the last decade as rhinologists have increasingly used topical steroid therapies and altered surgical techniques. It is important to understand the changes in success rates of surgery and frequency of revision endoscopic sinus surgery (ESS) in CRSwNP. The aim of this study was to retrospectively review the revision surgical rate of CRSwNP patients by evaluating outcomes in a cohort from the Medical University of South Carolina (MUSC). Methods: Retrospective review of CRSwNP patients operated upon at the MUSC between 2002 and 2019 by a single surgeon was performed. Assessed factors included demographics, comorbidities, CRSwNP subtype, extent of surgery, and steroid rinse compliance. Logistic regression was performed to identify factors associated with revision surgery. Results: Among 338 patients with at least 6 months of follow‐up, 24.9% had revision surgery, with a mean follow‐up of 52.6 months. In patients with any person‐time measure, the revision rate was 5.58 per 100 person‐years. Independent risk factors associated with increased odds ratio (OR) for revision surgery were: younger age (OR, 1.1); prior surgery (OR, 3.3); longer follow‐up (OR, 1.1); and surgery before 2009 (OR, 2.4) ( p < 0.05 for all). Conclusion: The revision surgery rate for CRSwNP was 24.9% among those with at least 6 months of follow‐up. Risk factors for higher revision rates included younger age, previous surgery, longer follow‐up, and surgery at the MUSC prior to 2009. As we enter an era of personalized medicine, it is important to consider patient‐ and surgeon‐specific factors, which impact revision surgery rates.